Åkerinäringens inställning till biodiesel - Magnusson, Daniel; Schotte, Peter (2011)

(untitled)
In Sweden, there an increasing need for transport and this leads directly to fuel demand of the transport sector is expected to increase. Both politicians and industry believes that renewable fuels are a realistic and significant method to reduce the transport sector's environmental impact. This study aims to document the Swedish haulage contractor’s attitude to biodiesel. Also to document the strengths and weaknesses of biodiesel, based on opinions from the ultimate consumers. Furthermore the study aims to identify a factor that controls the purchasers’ choice of fuel. The study was based on a consumer survey with several companies in the truck companies. The interviews of truck companies were conducted by telephone in the spring of 2011 and 14 respondents were selected by using a stratified sample to obtain demographic spread from north to south. Haulers believed that factors linked to price, availability and performance was relevant to the purchase of fuel. The investigation showed that if the haulage industry's customers were willing to pay the extra costs for increased environmental awareness and carbon-neutral transports. During these conditions the transport companies would be willing to pay for extra costs. Transport operators were not willing to buy more expensive fuels, provided that it was not economically justified by this choice generating increased revenue. Fifty percent of the truck companies in the study believed they would increase their fuel costs if they switched over to biodiesel. The truck companies considered that biodiesel not were corresponding to standard diesel in terms of quality. Availability was an important factor, thus transport companies were not willing to drive extra lines to fill up with biodiesel if they have standard diesel just around the corner.